Zakat Korporasi Dalam Kerangka Islamic Business Finance: Kajian Literatur Atas Konsep, Tata Kelola, dan Implikasinya di Indonesia - Tris Cahyawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Zakat is an Islamic social finance instrument that plays a vital role in wealth redistribution and social welfare enhancement. The development of modern business practices has encouraged the emergence of corporate zakat as a zakat obligation for business entities operating in accordance with Islamic values. This study aims to explain the concept of corporate zakat and analyze its position within the framework of Islamic Business Finance, including its management, governance, and implications for the economy and Islamic business practices in Indonesia. The study employs a narrative literature review based on secondary data obtained from academic journals, scholarly books, regulations, and official reports issued by zakat institutions in Indonesia, supported by relevant regional literature. The findings indicate that corporate zakat plays a strategic role as a mechanism for economic redistribution, strengthening Islamic business ethics, and providing a sustainable source of social financing within the Islamic financial ecosystem. Accountable, transparent, and Sharia-compliant governance is essential to enhance the effectiveness of corporate zakat management. The study highlights the importance of regulatory strengthening and synergy between corporations and zakat institutions to optimize the contribution of corporate zakat to equitable and sustainable Islamic economic development.